KELULUSHIDUPAN DAN PERTUMBUHAN BENIH IKAN LELE SANGKURIANG (Clarias gariepinus) YANG DIBERIKAN KEJUTAN LISTRIK 10, 15, 20 VOLT - Hendri, Afrizal; Samuki, Khairul; Mahendra, Mahendra; Diana, Farah (Universitas Teuku Umar, 2022)
The purpose of this study was to obtain an optimal growth rate on the provision of electric voltage and to determine the effect of applying an electric voltage to the survival pattern of sangkuriang catfish fry. This study used an experimental method with a completely randomized design (CRD) consisting of 4 treatments and 3 replications. The treatment given is an electric current voltage of 0 volts, 10 volts, 15 volts, and 20 volts. The test parameters in this study include survival, daily growth rate, biomass growth rate, feed conversion ratio, and feed efficiency. The results of the test parameters explained that the best electric current was the 15-volt treatment seen from the daily growth rate of 2.971%, the biomass growth rate of 0.874 g/day, feed conversion of 1.136 grams, and feeding efficiency of 88.227% while the best survival rate parameter was the 20-volt treatment. (P3) with a value of 63.33%. The results of this study had a positive impact on sangkuriang catfish seeds by applying an electric current to freshwater media of 15 volts (P>0.05).